The evolution of intracranial aneurysm research from 2012 to 2021: Global productivity and publication trends - Zhang, Qian; Weng, Ling; Li, Jian (Frontiers in Neurology, 2022)
Background This study aimed to analyze the global research trends and map the knowledge network of intracranial aneurysm (IA) research in the last 10 years. Methods Publications related to IA from 2012 to 2021 were retrieved from the Web of Science core collection. Microsoft Excel 2010 and VOSviewer were used to characterize the largest contributors, including authors, journals, institutions, and countries. CiteSpace and VOSviewer were adopted to analyze the trends and knowledge network of IA. Results A total of 5,406 publications related to IA from 2012 to 2021 were identified, increasing from 344 in 2012 to 762 in 2021. Siddiqui, AH from the USA contributed the most publications. Papers published in the journal World Neurosurgery ranked first in quantity, while Stroke ranked first for total citations and citations per publication. The top three prolific institutions were Capital Medical University, Mayo Clinic, and the University Department of Neurology Utrecht from 2012 to 2021. Moreover, the USA held the greatest share in the field, and China was almost on par with the USA due to its rapid growth. Specifically, the most frequently covered topics over the recent decade were subarachnoid hemorrhage, endovascular treatment (EVT), clipping, vascular disorders, flow diverter, stent, delayed cerebral ischemia, inflammation, and hemodynamics. Conclusion The contribution made by different countries, institutions, journals, and authors for IA research over the past decade was demonstrated in the paper. The main topics include the choice of EVT or surgical clipping, particularly the application of flow diverter and associated complications, while themes such as the etiopathogenetic features of IA (e.g., inflammation and hemodynamics) deserve more attention.